From Policy to Pedagogy: Religious Moderation as a Counter-Radicalization Strategy in Islamic Education — A Systematic Literature Review - Prasetyo, Gatot; Fauziah, Yanuar Rizki; Syafii, Ahmad (Jurnal Pendidikan Islam, 2025)
Purpose – This study maps current evidence on religious moderation in Islamic Education in Indonesia to assess the effectiveness of policy, curriculum, pedagogy, and the institutional ecosystem—framed by Pancasila—as a counter-radicalization strategy and a shaper of inclusive character. Design/methods/approach – Systematic Literature Review (SLR) grounded in Kitchenham & Charters. Scopus search (February 12, 2025) using TITLE-ABS-KEY("religious" AND "moderation"), period 2018–2025, document type article. 754 articles found; 127 filtered as relevant; 72 fully reviewed; 2 excluded (review-based); 70 analyzed through qualitative content analysis (mechanical and interpretive stages) following the PRISMA scheme. Findings – Implementation of moderation is effective when wasathiyah values are integrated across subjects and practiced through dialogic methods (problem solving, inquiry, discussion), an integrative curriculum, and educator involvement. As a counter-radicalization strategy, effectiveness is supported by firm campus policies framed by Pancasila, the strengthening of national values (tawassuth, tawazun, i‘tidal, al-wathaniyah), and the role of madrasahs and universities as agents of social change. Key factors include school leadership, an inclusive curriculum, interfaith dialogue, and directed use of technology (Technological Pedagogical Content Knowledge [TPACK]). These findings sequentially answer RQ1–RQ4 (curriculum implementation; counter-radicalization strategies; contributions of empirical approaches; the role of higher education). Research implications – Recommendations include the standardization of moderation competencies in the Islamic Religious Education (PAI)/higher-education curriculum; the design of dialogic pedagogy grounded in experiential learning and inclusive social projects; capacity building for educators and digital literacy (TPACK); and institutional policies that synergize mentoring, intra/extracurricular activities, anti-radicalization governance, and curation of the educational digital ecosystem.